Specific plasma lipid classes and phospholipid fatty acids indicative of dairy food consumption associate with insulin sensitivity - Nestel, Paul John; Straznicky, Nora; Mellett, Natalie Ann; Wong, Gerard; De Souza, David Peter; Tull, Dedreia Lorraine; Barlow, Christopher Kenneth; Grima, Mariee Teresa; Meikle, Peter John (The American journal of clinical nutrition, 2014)
Background: Reports have suggested that the consumption of dairy foods may reduce risk of type 2 diabetes on the basis of evidence of raised circulating ruminant fatty acids.Objective: We determined whether certain phospholipid species and fatty acids that are associated with full-fat dairy consumption may also be linked to diminished insulin resistance.Design: Four variables of insulin resistance and sensitivity were defined from oral-glucose-tolerance tests in 86 overweight and obese subjects with metabolic syndrome. Plasma phospholipids, sphingolipids, and fatty acids were determined by using a lipidomic analysis and gas chromatography–mass spectrometry to provide objective markers of dairy consumption. Food records provided information on dairy products. Associations were determined by using linear regression analyses adjusted for potential confounders age, sex, systolic blood pressure, waist:hip ratio, or body mass index (BMI) and corrected for multiple comparisons.Results: Lysophosphatidylcholine, lyso-platelet-activating factor, and several phospholipid fatty acids correlated directly with the number of servings of full-fat dairy foods. Lysophosphatidylcholine and lyso-platelet-activating factor were also associated directly with insulin sensitivity when accounting for the waist:hip ratio (Matsuda index unadjusted, P < 0.001 for both; adjusted for multiple comparisons, P < 0.02 for both) and inversely with insulin resistance (fasting insulin unadjusted, P < 0.001 for both; adjusted, P = 0.04 and P < 0.05, respectively; homeostasis model assessment of insulin resistance adjusted, P = 0.04 for both; post–glucose insulin area under the plasma insulin curve during the 120 min of the test adjusted, P < 0.01 for both). The substitution of BMI for the waist:hip ratio attenuated associations modestly. Phospholipid fatty acid 17:0 also tended to be associated directly with insulin sensitivity and inversely with resistance.Conclusion: Variables of insulin resistance were lower at higher concentrations of specific plasma phospholipids that were also indicators of full-fat dairy consumption. This trial was registered at clinicaltrials.gov as NCT00163943.